Optimizing sustainable consumption: Understanding reusable lunch box usage intentions through the theory of planned behavior - Jayanthi, Luh De Dwi (Waste Handling and Environmental Monitoring, 2025)
Background: The shift from using single use to reusable lunch boxes presents a challenge for college students. The economic circular framework is now applied not only to industrial processes but also to consumption behavior. This study aims to examine how the Theory of Planned Behavior (TPB) model, including attitude, subjective norms, perceived behavioral control, moral norms, descriptive norms, and self-identity, influences the intention to use reusable lunch boxes. Method: The study involved 110 undergraduate students from a college campus in Denpasar City. Participants completed questionnaires distributed using a snowball sampling technique. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings: The study found that perceived behavioral control and self-identity significantly affect the intention to use reusable lunch boxes. The R-square analysis indicated that 31.1% of students' intention to use reusable lunch boxes was influenced by subjective norms, while 26.4% was influenced by self-identity. Conclusion: The study concludes that perceived behavioral control and self-identity play key roles in students' intention to use reusable lunch boxes. Future research should focus on making reusable lunch boxes more convenient and integrating them into a system that encourages behavior change on college campuses. Novelty/Originality of this article: This study applies the Theory of Planned Behavior to understand college students' intentions to adopt reusable lunch boxes, offering valuable insights for promoting sustainable consumption behavior in a campus setting.